Analisis Pendekatan Saintifik Dalam Pembelajaran Tematik di Kelas IV MIS Al-Ikhlasiah Medan Sunggal - Arima Yanti Saragih; Halwa Tamara; Nur Khalizah Tanjung; Putri Amelia Lubis; Aufa Aufa (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Research entitled "Analysis of Application of Scientific Approach to Science Learning in Grade 4 SD/MIS AL-IKHLASIAH". This study aims to determine how the achievement of scientific application that has been applied in the school. The condition of students learning is not yet fully implementing scientific steps such as observing, asking, trying, associating, and communicating in accordance with the demands of the 2013 curriculum. Lack of practicum in learning, because it only focuses on books that have been provided by the school, students only read and do not have an understanding of the meaning followed by the teacher asking questions. Impact on students' lack of ability in understanding the concept of the material. This condition must be solved because it has an impact on the students lack of ability in understanding the concept of the material. In solving problems, one of the actions that can be taken is to apply a scientific approach to learning that is appropriate and can help students be able to learn in a fun, meaningful, active way, be directly involved in concept discovery independently and can increase students' curiosity about learning materials. Keywords: Analysis, Scientific Approach, Thematic Approac.